Political Communication Contract on Instagram: A Semiolinguistic Analysis - Pimenta, Lidiane Reis Alves; Silva, Luciana Soares da (Redis: Revista de Estudos do Discurso, 2024)
This article examines the structure of political discourse conveyed on Instagram to infer how the political communication contract is established on this social network platform. This study is theoretical, methodological, and qualitative and based on concepts of Discourse Analysis developed by Charaudeau (1983) within the framework of his Semiolinguistic Theory. To understand the notions of political discourse and political communication contracts with their strategies, we rely on Charaudeau (2018). To understand the particularities of Instagram as a device for the creation and dissemination of political discourse, we looked for a theoretical apparatus in the works of Piovezani Filho (2007), Castells (2021), Charaudeau (2018) and Recuero, Bastos and Zago (2020). In this investigation, we found that the political discourse broadcast on Instagram follows the structure of the political communication contract, but due to technological, cultural and social changes, this discourse has transformed to adapt to the characteristics of the web, a space in which fluidity, creativity, and dynamism are valued. This study concludes that Instagram presents itself as a powerful and important device in political strategy that is capable of reaching many users of these networks and potential voters, combining the structuring characteristics of the political communication contract with strategies inherent to the webspace, which makes Instagram a permanent platform.